THE EFFECT OF DEMOGRAPHIC FACTORS ON PEOPLE’S MOTIVATION IN EXECUTING HOUSEHOLD ACCOUNTING - Teerakanon, Attapong (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2020)
This research aimed at 1) studying the people’s demographic factors and motivation for household accounting execution and 2) comparing the motivation in household accounting execution classified by people’s demographic factors in Thanyaburi District, Pathum Thani province. The samples were of 137 people living in Thanyaburi municipality, Pathum Thani. The data collection employed questionnaires with purposive sampling and convenience sampling method. The statistics used in data analysis included descriptive statistics covering frequency, percentage, mean, and standard deviation and inferential statistics covering the Independent Sample t-test and One-Way ANOVA at the statistical significance level of 0.05. The results showed that most respondents were female, aged 20 - 29 years old, were student, graduated from bachelor’s degree, earned between 10,001 - 15,000 baht and expensed between 5,000 and 10,000 baht. People had opinion about motivation in household accounting execution in terms of benefits, patterns and methods and support from government agencies and others in high level. After hypothesis testing, the study revealed that people with different demographic factors in terms of age, education, monthly household income and monthly household expenditure had motivation toward benefits, patterns and methods and support from government agencies and others differently at the statistically significant level as of 0.05.